2021
DOI: 10.1016/j.toxrep.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant study of polyphenol from red seaweeds dichotomously branched gracilaria Gracilaria edulis and robust sea moss Hypnea valentiae

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In addition, signals specific to aromatic rings were observed, such as the band at 1693 cm −1 corresponding to C=C stretching, the signal at 1453 cm −1 is due to C-C stretching and, finally, the signal at 1034 cm −1 is attributed to C-O stretching. All these bands show the presence of polyphenols in the extract obtained [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, signals specific to aromatic rings were observed, such as the band at 1693 cm −1 corresponding to C=C stretching, the signal at 1453 cm −1 is due to C-C stretching and, finally, the signal at 1034 cm −1 is attributed to C-O stretching. All these bands show the presence of polyphenols in the extract obtained [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols from red algae carry potential assets, as they may have a strong pharmaceutical value in the future. Biochemical analysis revealed the presence of flavonoids, saponins, tannin, and steroids in both red algae, while only G. edulis revealed phenolics and alkaloids [ 71 ].…”
Section: Antimicrobial Activity From Rhodophyta and Chlorophyta Extractsmentioning
confidence: 99%
“…It was previously reported that the TPC of Fucus spiralis could be as high as 1.15 ± 0.06 mmol GAE/g dry weight, which is equivalent to 195.6 ± mg.GAE/g extract [28]. In light of the previous studies and evidence, it appears that the natural phenolic grouped compounds in flavonoids show anticancer, anti-inflammatory, antihypertensive, antioxidative, and antiproliferative properties [29][30][31].…”
Section: Phytochemical Test Of P Hornemanniimentioning
confidence: 99%